Pneumococcal Serotype 5 Colonization Prevalence Among Newly Arrived Unaccompanied Children 1 Year After an Outbreak—Texas, 2015. Issue 2 (February 2017) - Kobayashi, Miwako; Misegades, Lara; Fleming-Dutra, Katherine E.; Ahmed, Sana; Gierke, Ryan; Nanduri, Srinivas; Healy, Jessica M.; Nguyen, Duong T.; da Gloria Carvalho, Maria; Pimenta, Fabiana; Waterman, Stephen H.; Moore, Matthew R.; et al.
Abstract : In 2014, an acute respiratory illness outbreak affected unaccompanied children from Central America entering the United States; 9% of 774 surveyed children were colonized with Streptococcus pneumoniae serotype 5. In our 2015 follow-up survey of 475 children, serotype 5 was not detected, and an interim recommendation to administer 13-valent pneumococcal conjugate vaccine to all unaccompanied children was discontinued.